HEART TRANSPLANTATION IN PATIENT WITH POST-RUPTURE PSEUDOANEURYSM OF SEGMENTAL BRANCH OF PULMONARY ARTERY - M. L. Gordeev; G. V. Nikolaev; A. E. Bautin; I. Yu. Kasherininov; S. V. Datsenko; D. M. Tashkhanov; A. S. Iakovlev; A. V. Naimushin; E. Ya. Malaya; V. E. Rubinchik; I. V. Sukhova; P. A. Fedotov (Вестник трансплантологии и искусственных органов, 2014)
Right heart catheterization (RHC) should be performed on all candidates in preparation for listing for cardiac transplantation. Patient, 64 y. o., with chronic heart failure NYHA III class, had developed a rare complication while performing that procedure – a rupture of segmental branch of pulmonary artery (PA) with pulmonary haemorrhage. The episode of pulmonary bleeding was stopped conservatively without surgical management. There was a pseudoaneurysm formation of segmental branch of PA 2,7 × 2,8 cm with signs of thrombosis. Afterfi ve months the patient underwent heart transplantation without severe complications in perioperative period. No more recurrent episodes of pulmonary haemorrhage were identifi ed.